Dilution cultivation of marine heterotrophic bacteria abundant after a spring phytoplankton bloom in the North Sea. (5th May 2014) - Hahnke, Richard L.; Bennke, Christin M.; Fuchs, Bernhard M.; Mann, Alexander J.; Rhiel, Erhard; Teeling, Hanno; Amann, Rudolf; Harder, Jens
Summary: The roles of individual bacterioplankton species in the re‐mineralization of algal biomass are poorly understood. Evidence from molecular data had indicated that a spring diatom bloom in the German Bight of the North Sea in 2009 was followed by a rapid succession of uncultivated bacterioplankton species, including members of the genera U lvibacter, F ormosa, P olaribacter (class F lavobacteria ) and R einekea (class G ammaproteobacteria) . We isolated strains from the same site during the diatom bloom in spring 2010 using dilution cultivation in an artificial seawater medium with micromolar substrate and nutrient concentrations. Flow cytometry demonstrated growth from single cells to densities of 10 4 –10 6  cells ml –1 and a culturability of 35%. Novel F ormosa, P olaribacter and R einekea strains were isolated and had 16S rRNA gene sequence identities of > 99.8% with bacterioplankton in spring or summer 2009. Genomes of selected isolates were draft sequenced and used for read recruitment of metagenomes from bacterioplankton in 2009. Metagenome reads covered 93% of a F ormosa clade B, 91% of a R einekea and 74% of a F ormosa clade A genome, applying a ≥ 94.5% nucleotide identity threshold. These novel strains represent abundant bacterioplankton species thriving on coastal phytoplankton blooms in the North Sea.